Kemampuan Laba dan Arus Kas dalam Memprediksi Laba dan Arus Kas Perusahaan Go Publik di Indonesia - Parawiyati Parawiyati; Zaki Baridwan (The Indonesian Journal of Accounting Research, 2013)
Financial accounting information is used by potential users to make necessary economic decisions. Earnings and cash flow are some of the measure that show a firms successful management. Earnings are useful for measuring a firms performance, and estimating the representative earning, the risk of investing and the cash flow information key measures of liquidity. Accounting information, is not yet one of the fundamental analysis tools for trading in Indonesian Capital     Market. However, with increased development, accounting information will be necessary for making important decisions in the capital market.The objective of the study was to test the relationship of the ability of financial information in predicting the benefit of equity investment that consists of earnings and cash flow. The first hypothesis is earning predictor is better than cash flow predictor to predict future earning. Second, earning predictor is better than cash flow predictor to predict future to predict future cash flow. Lastly, earnings have incremental prediction ability to cash flow.There were 288 financial statements of manufacturing firms for the period of 1989-1994 include as a sample. Earnings data used in the tests is from the period of 1989-1994 and cash flow data is from 1992-1994 period. The statistical method used in this research is linear regression. then T-test, regression coefficient,     correlation determination and F-test on the 5% level significance. The autocorrelation tests show that there is no linear relationship between independent variables, and that there was no correlation between disturbance factors, because the Durbin Waston test shows value of 2.The statistical results show that earning predictor and cash flow predictor are both significant in predicting earning and cash flow one year ahead, The ability of earning predictor in predicting earning and cash flow is bigger than cash flow predictor, this is shown with the regression coefficient. Then is showed that a part from earnings being a tool for predicting earnings, it can be predict cash flows. The results of this research also show F-test is significant, which means that both predictors, earning and cash flow can be used for predicting earning and cash flow efficiently.Key Words:    Auditors Ethical Orientation, Ethical Sensitivity, Professional   Commitment, Organization Commitment